Smelting separation behaviors and mechanisms of high-alumina rich-manganese ore obtained from metallic reduction and magnetic separation - Gao L.-H.; Liu Z.-G.; Chu M.-S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this paper the smelting separation of high-alumina rich-manganese ore prepared with selective reduction and magnetic separation was proposed to produce the high carbon ferromanganese alloy (HCFeMn). The rational smelting separation parameters for high-alumina rich-manganese ore included the FC/O of 1.1, the smelting temperature of 1550°C, the smelting time of 60 min, and the basicity of 0.7. The smelting separation of high-alumina rich-manganese ore was achieved successfully. The content of Fe, C, Si and other impurities (P, S) were 12.13%, 6.73%, 0.17% and 0.14, 0.008, respectively. Especially, the recovery and the content of Mn reached 80.47% and 76.76%. The obtained high carbon ferromanganese alloy met the higher standard (FeMn78C8) of ferromanganese alloy, especially the content of Si P and S in the HCFeMn alloy was far below the standard value. Based on the SEM-EDS, XRD and thermodynamic calculation, the smelting and separation mechanisms of high-alumina rich-manganese ore was proposed to more effectively explain the effect of smelting parameters on slag/metal separation behaviors during the process of smelting HCFeMn alloys.